6(y+9)+y=4(y+4)-2

Simple and best practice solution for 6(y+9)+y=4(y+4)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y+9)+y=4(y+4)-2 equation:


Simplifying
6(y + 9) + y = 4(y + 4) + -2

Reorder the terms:
6(9 + y) + y = 4(y + 4) + -2
(9 * 6 + y * 6) + y = 4(y + 4) + -2
(54 + 6y) + y = 4(y + 4) + -2

Combine like terms: 6y + y = 7y
54 + 7y = 4(y + 4) + -2

Reorder the terms:
54 + 7y = 4(4 + y) + -2
54 + 7y = (4 * 4 + y * 4) + -2
54 + 7y = (16 + 4y) + -2

Reorder the terms:
54 + 7y = 16 + -2 + 4y

Combine like terms: 16 + -2 = 14
54 + 7y = 14 + 4y

Solving
54 + 7y = 14 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
54 + 7y + -4y = 14 + 4y + -4y

Combine like terms: 7y + -4y = 3y
54 + 3y = 14 + 4y + -4y

Combine like terms: 4y + -4y = 0
54 + 3y = 14 + 0
54 + 3y = 14

Add '-54' to each side of the equation.
54 + -54 + 3y = 14 + -54

Combine like terms: 54 + -54 = 0
0 + 3y = 14 + -54
3y = 14 + -54

Combine like terms: 14 + -54 = -40
3y = -40

Divide each side by '3'.
y = -13.33333333

Simplifying
y = -13.33333333

See similar equations:

| 9x^2+4x-4=3x^2 | | 1-2x+3=12 | | 2v-16=2 | | 8.25y=-115.5 | | 1-5x-6x=-10 | | 36-1/26(4x)=27-1/26(3x) | | 4x-7=2x-4 | | x+iy=4-2i | | y^2+19y+84= | | 7(1-2x)=-6x-33 | | 62=8n-2 | | 2(x+1)=x-9 | | 8x-7w+4x+8y+3y+5w= | | -x-17=-4x+1 | | c+18=50 | | -6=2z+14 | | 4x-1+2x=5x+4x | | 1.16x=5.80 | | -y+7=2y+7 | | 35-3v=2v+5 | | 8x+2(-5-3x)=8-7x | | 0=7w-34 | | 6y-42=5y+20 | | b-14=28 | | 6n^2+18n=0 | | 3n+10=91 | | 3(x+3)=14 | | (12m-10)(10m+10)= | | 10x-9y+13=0 | | 4m+2=30 | | 5(8-6x)=-7x+2(-8x-8) | | -0.1x-5x=-18.87 |

Equations solver categories